2019
DOI: 10.3390/ijerph16244921
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Precariousness of Nursing Staff in Catalonia’s Public and Private Nursing Homes

Abstract: Nursing staff who provide care in the nursing homes of Catalonia have more precarious work conditions, including more demanding schedules and work overload, than those in other areas of care. This situation entails two major problems: Detrimental health results for nurses who face psychosocial and physical risks and a negative impact on the care provided to patients, with a decrease in the quality of care. This study aimed to describe the precarious employment situation of nursing staff in nursing homes. We ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 28 publications
3
26
1
5
Order By: Relevance
“…In addition, the working environment might be more sympathetic due to differences in their management systems, more horizontal vs. more vertical organisation, for example. It has been shown that care aides in privately run nursing homes suffer greater job insecurity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the working environment might be more sympathetic due to differences in their management systems, more horizontal vs. more vertical organisation, for example. It has been shown that care aides in privately run nursing homes suffer greater job insecurity [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ruiz-Fernández et al [ 21 ] examine the quality of life and associated factors among nurses in the public health service, while another set of studies analyses the same elements in the field of long-term care. Fité-Serra et al [ 22 ] focus on the working conditions of nursing staff in care homes. Sarabia-Cobo et al [ 23 ] study the relationship between stress and quality of life in psychogeriatric professionals, and Briones-Peralta et al [ 24 ] analyse the job satisfaction of carers in a nursing home for older persons with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies in high-income countries, including a range of welfare states regimes ( Navarro et al., 2006 ), such as the US, Spain, South Korea or Finland, show that PE is quite common among HCWs ( Han et al., 2009 , C. Muntaner et al., 2006 , Fité-Serra et al., 2019 ). Research examining specific healthcare sectors and type of work, suggest several determinants of PE and their association with a range of poor health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Supply and demand of nursing homes differ across countries, but all are concerned about the quality of care provided in these homes (Scheil-Adlung, 2015), and policy decision makers face common issues of workforce capacity. Globally, there is a shortage of nursing assistants in nursing homes (International Labour Organization, 2018) that is related to numerous factors, including the increasing complexity of care, the lack of resources to provide quality care (Eurofund, 2017), and the precariousness of their work (Fite-Serra et al, 2019). Addressing health care human resource issues in nursing homes calls for a global approach.…”
Section: Introductionmentioning
confidence: 99%